Corncob-based hard carbon material as well as preparation method and application thereof
By mixing corn cobs with monosaccharides and carbonizing and heat treatment, corn cob-based hard carbon materials with high sodium storage capacity were prepared, which solved the problem that sodium ion batteries in the prior art are difficult to simultaneously improve the first Coulomb efficiency and specific capacity after multiple cycles, and achieved efficient electrochemical performance.
Patent Information
- Application Number
- CN202411716093.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-04-04
AI Technical Summary
The existing sodium ion batteries made of corncob-based hard carbon materials are difficult to maintain good specific capacity after multiple cycles while high first Coulomb efficiency.
By mixing corn cobs with monosaccharides and carbonizing them, then insulated at 1400-1500°C, and cooling to 500-800°C at a rate of 1-2°C/min, corn cob-based hard carbon material with high sodium storage capacity was prepared.
It achieves high first Coulomb efficiency of sodium ion batteries and high specific capacity after multiple cycles, and also has good rate performance.
Smart Images

Figure CN119750539A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of sodium ion battery manufacturing, and more specifically, to a corncob-based hard carbon material and a preparation method and application thereof. Background Art
[0002] In order to increase the utilization of renewable energy and reduce carbon emissions, it is crucial to develop more efficient and economical energy storage technologies. Due to its high reversible capacity and long cycle life, electrochemical energy storage technology based on rechargeable batteries has shown great application potential in the field of energy storage. Metallic sodium is abundant and inexpensive in nature, making it an ideal material to replace lithium. In order to meet people's demand for high energy density sodium-ion batteries, improving the first coulombic efficiency of sodium-ion batteries and the specific capacity after multiple cycles has become an important research direction for sodium-ion batteries.
[0003] In recent years, hard carbon has gradually attracted the attention of researchers as a negative electrode material for sodium-ion batteries due to its high specific capacity and low redox potential, as well as large interlayer spacing and rich pore structure. Compared with organic polymers, biomass raw materials are ubiquitous in nature as hard carbon precursors, and have the advantages of easy availability, low cost, environmental friendliness, and high carbon content. At present, the method of increasing sodium storage sites is generally used to increase the specific capacity, but this method is often accompanied by an increase in specific surface area. The larger specific surface area will aggravate the decomposition of the electrolyte on the electrode surface, produce a large amount of irreversible capacity in the first cycle, and result in a low first coulombic efficiency. Therefore, it is difficult for existing biomass hard carbon materials to maintain a good specific capacity while also having a high coulombic efficiency.
[0004] For example, an existing patent discloses a method for preparing nitrogen-sulfur doped corncob-based hard carbon negative electrode materials, which improves the slope capacity of sodium-ion batteries by doping heteroatoms (nitrogen and sulfur). However, the first coulombic efficiency of sodium-ion batteries made from corncob-based hard carbon negative electrode materials prepared by this method is significantly low, and the method only studies the specific capacity after 50 cycles, without further examining the specific capacity after more cycles.
[0005] Therefore, there is an urgent need to find a new technology to enable sodium ion batteries made of corncob-based hard carbon materials to have high first coulombic efficiency and maintain good specific capacity after multiple cycles. Summary of the invention
[0006] The primary purpose of the present invention is to overcome the problem that the sodium ion battery made of the corncob-based hard carbon material prepared above is difficult to have a high first coulombic efficiency and maintain a good specific capacity after multiple cycles, and to provide a method for preparing a corncob-based hard carbon material. The preparation method uses corncobs as biomass materials, first mixes them with monosaccharides and then carbonizes them, then performs heat preservation treatment at a certain temperature, and then cools to 500-800°C at a rate of 1-2°C / min. The prepared corncob-based hard carbon material is made into a sodium ion battery with a high first coulombic efficiency and a high specific capacity after multiple cycles. In addition, the sodium ion battery made of the corncob-based hard carbon material prepared by the present invention also has good rate performance.
[0007] A further object of the present invention is to provide a corncob-based hard carbon material prepared by the above preparation method.
[0008] Another object of the present invention is to provide an application of the above corncob-based hard carbon material in preparing a negative electrode for a sodium ion battery.
[0009] Another object of the present invention is to provide a negative electrode for a sodium ion battery.
[0010] Another object of the present invention is to provide a sodium ion battery.
[0011] The above-mentioned object of the present invention is achieved by the following technical solutions:
[0012] A method for preparing a corncob-based hard carbon material comprises the following steps:
[0013] S1. corn cobs and monosaccharides are mixed to obtain a mixture;
[0014] S2. carbonizing the mixture to obtain a carbonized material;
[0015] S3. The carbonized material is heat treated and cooled to obtain the corncob-based hard carbon material;
[0016] The heat treatment process in step S3 is: firstly heating the carbonized material to 1400-1500°C to keep the temperature, and then cooling it to 500-800°C at a rate of 1-3°C / min.
[0017] The inventors of the present invention discovered through research that when corn cobs are used as biomass materials, they are first mixed with monosaccharides and then carbonized. The monosaccharides decompose during the carbonization process to form pore structures. These pore structures can be used as storage spaces for sodium ions, thereby improving the sodium storage capacity of corn cob-based hard carbon materials, and thus enabling sodium ion batteries to still have a high specific capacity after multiple cycles. At the same time, the first coulombic efficiency of sodium ion batteries can also be improved to a certain extent.
[0018] The inventors of the present invention continued to study and found that by heat-insulating the carbonized material at a certain temperature (1400-1500°C) and controlling the rate of cooling to 500-800°C after heat insulation, the initial coulombic efficiency of the sodium ion battery and the specific capacity after multiple cycles can be further improved. The reason may be: heat-insulating at a certain temperature (1400-1500°C) can increase the porosity of the corn cob-based hard carbon material and expand the interlayer spacing of the corn cob-based hard carbon material; controlling the cooling rate from 1400-1500°C to 500-800°C in step S3 within a certain range can keep the porosity and interlayer spacing of the corn cob-based hard carbon material good, avoid the destruction of these microstructures caused by rapid cooling, and help the storage and transmission of sodium ions, thereby improving the initial coulombic efficiency of the battery and the specific capacity after multiple cycles.
[0019] If the holding temperature of the heat treatment is too high or too low, it is not conducive to improving the porosity and interlayer spacing of the corncob-based hard carbon material.
[0020] If the cooling rate is not controlled to drop to 500-800°C after insulation at 1400-1500°C, but is directly cooled naturally (the cooling rate of natural cooling is relatively high, about 5°C / min), the microstructure formed under the insulation at 1400-1500°C will be destroyed, resulting in lower initial coulombic efficiency of the battery and lower specific capacity after multiple cycles.
[0021] If step S1 does not use monosaccharides but uses disaccharides (such as sucrose), since disaccharides have a poor pore-forming effect on corn cobs, the initial coulombic efficiency and the specific capacity after multiple cycles of the sodium ion battery are both low.
[0022] Preferably, in step S1, the mass ratio of the corn cob to the monosaccharide is 1:(0.5-2).
[0023] Preferably, in step S1, the monosaccharide is one or both of fructose and glucose.
[0024] Preferably, in step S1, before the mixing, the step of drying the corn cobs is also included.
[0025] More preferably, the drying process is: drying the corn cob at 50-120° C. for 24-96 hours.
[0026] More preferably, the method further includes the step of crushing the corn cobs before drying.
[0027] Preferably, in step S1, the mixing method is ball milling.
[0028] More preferably, the ball milling conditions are: a rotation speed of 500 to 800 r / m and a time of 6 to 12 h.
[0029] Preferably, in step S2, the carbonization temperature is 500-600°C.
[0030] More preferably, in step S2, the temperature is raised from room temperature to the carbonization temperature at a rate of 1-5°C / min.
[0031] Preferably, in step S2, the carbonization time is 2 to 3 hours.
[0032] Preferably, in step S2, the carbonization further includes pickling treatment.
[0033] More preferably, the acid in the pickling treatment is at least one of hydrochloric acid or sulfuric acid.
[0034] More preferably, the concentration of the acid in the pickling treatment is 0.5 to 3 mol / L.
[0035] More preferably, the process of the pickling treatment is: adding the carbonized material into an acid solution and stirring at 50-60° C. for 12-24 hours.
[0036] More preferably, the pickling treatment further includes washing and drying steps.
[0037] Further preferably, the washing process is: adding water to the carbonized material and filtering.
[0038] Further preferably, the drying process is: drying at 60-100° C. for 24-96 hours.
[0039] Preferably, the carbonization process in step S2 and the heat treatment process in step S3 are performed under an atmosphere of protective gas.
[0040] More preferably, the protective gas is at least one of nitrogen, argon or helium.
[0041] Preferably, in step S3, the heat treatment process is: firstly heating the carbonized material from room temperature to 1400-1500°C at a rate of 1-3°C / min for 2-3h, and then cooling the carbonized material to 500-800°C at a rate of 1-2°C / min.
[0042] Preferably, in step S3, the cooling further includes a ball milling step.
[0043] More preferably, the ball milling conditions are: a rotation speed of 500 to 800 r / m and a time of 6 to 12 h.
[0044] The present invention also protects a corncob-based hard carbon material prepared by the above preparation method.
[0045] The present invention also protects the use of the corncob-based hard carbon material in preparing a negative electrode of a sodium ion battery.
[0046] The present invention also protects a sodium ion battery negative electrode, which comprises the above-mentioned corncob-based hard carbon material.
[0047] Preferably, the sodium ion battery negative electrode further includes a conductive agent, a binder and a current collector.
[0048] More preferably, the mass ratio of the corncob-based hard carbon material, the conductive agent and the adhesive is (92-97): (1-5): (1-5).
[0049] More preferably, the adhesive is a mixture of carboxymethyl cellulose and styrene-butadiene rubber.
[0050] More preferably, the conductive agent is conductive carbon black.
[0051] More preferably, the current collector is copper foil.
[0052] The present invention also protects a sodium ion battery, which comprises the above-mentioned sodium ion battery negative electrode.
[0053] Compared with the prior art, the present invention has the following beneficial effects:
[0054] The present invention uses corn cobs as biomass materials, first mixes with monosaccharides and then carbonizes them, then performs heat preservation treatment at a certain temperature, and then cools to 500-800°C at a rate of 1-2°C / min. The sodium ion battery made of the corn cob-based hard carbon material has a high first coulomb efficiency and a high specific capacity after multiple cycles. In addition, the sodium ion battery made of the corn cob-based hard carbon material prepared by the present invention also has good rate performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0055] Figure 1 The corncob-based hard carbon material prepared in Example 1 is used to make a battery at 20-1500 mAg -1 Charge and discharge rate performance diagram under current density.
[0056] Figure 2 The corncob-based hard carbon material prepared in Example 1 was used to make a battery at 300 mAg -1 Charge and discharge cycle performance diagram under current density. DETAILED DESCRIPTION
[0057] In order to more clearly and completely describe the technical solution of the present invention, the present invention is further described in detail through specific embodiments below. It should be understood that the specific embodiments described herein are only used to explain the present invention, and are not used to limit the present invention. Various changes can be made within the scope of the rights of the present invention.
[0058] Example 1
[0059] This embodiment provides a method for preparing a corncob-based hard carbon material, comprising the following steps:
[0060] 1) Weigh 10 g corncob powder, crush it three times in a grinder, and then dry it in a drying oven at 100°C for 48 hours. Put the dried corncob powder and 10 g glucose into a ball mill and mill them (30 minutes per rotation and 30 minutes per stop) at a rotation speed of 500 r / m and a ball milling time of 12 hours to obtain a mixture.
[0061] 2) The mixture was heated to 600° C. at 2° C. / min in a nitrogen atmosphere for carbonization, kept at this temperature for 3 h, and naturally cooled to room temperature to obtain a carbonized material.
[0062] 3) The carbonized material was added to a 1 mol / L hydrochloric acid solution, stirred at 60°C for 24 h, filtered four times, 2000 mL of deionized water was added each time, and dried at 80°C for 48 h.
[0063] 4) The carbonized material treated in step 3) is heat treated in a nitrogen atmosphere. The heat treatment process is: heating from 25°C to 1500°C at 2°C / min for 2h, and then cooling to 600°C at 2°C / min. Then naturally cool to room temperature, put into a ball mill for ball milling (30 minutes per rotation, 30 minutes per stop), the ball milling speed is 500r / m, and the ball milling time is 6h, and the corncob-based hard carbon material is obtained.
[0064] Example 2
[0065] This embodiment provides a method for preparing a corncob-based hard carbon material. The difference from Embodiment 1 is that the heat treatment process in step 4) is: heating from 25°C to 1500°C at 2°C / min and keeping it for 2h, and then cooling to 500°C at 1°C / min.
[0066] Example 3
[0067] This embodiment provides a method for preparing a corncob-based hard carbon material. The difference from Embodiment 1 is that the heat treatment process in step 4) is: heating from 25°C to 1400°C at 2°C / min and keeping it for 2h, and then cooling to 600°C at 2°C / min.
[0068] Comparative Example 1
[0069] This comparative example provides a method for preparing a corncob-based hard carbon material. The difference from Example 1 is that glucose is not added in step 4).
[0070] Comparative Example 2
[0071] This embodiment provides a method for preparing a corncob-based hard carbon material. The difference from Embodiment 1 is that the heat treatment process in step 4) is: heating from 25°C to 1300°C at 2°C / min and keeping it for 2h, and then cooling to 600°C at 2°C / min.
[0072] Comparative Example 3
[0073] This embodiment provides a method for preparing a corncob-based hard carbon material. The difference from Embodiment 1 is that the heat treatment process in step 4) is: heating from 25°C to 1600°C at 2°C / min and keeping it for 2h, and then cooling to 600°C at 2°C / min.
[0074] Comparative Example 4
[0075] This comparative example provides a method for preparing a corncob-based hard carbon material. The difference from Example 1 is that the heat treatment process in step 4) is: heating from 25°C to 1500°C at 2°C / min and keeping the temperature for 2h. Then naturally cooling to room temperature. The rate of natural cooling to room temperature is about 5°C / min. That is, this comparative example does not control the cooling rate of the process from 1500°C to 600°C.
[0076] Performance Testing
[0077] The corncob-based hard carbon material prepared in Example 1 and Comparative Examples 1 to 4 was dissolved in deionized water with conductive carbon black, CMC, and adhesive styrene-butadiene rubber in a mass ratio of 94:2:4:2 and stirred to obtain a slurry. The slurry was coated on a copper foil and vacuum dried for 12 hours to obtain a test electrode sheet. The battery was assembled in an argon-filled glove box. The battery consisted of a test electrode sheet, a reference electrode sheet, a diaphragm, and an electrolyte. The sodium sheet was used as the reference electrode sheet, the diaphragm was glass fiber, and the electrolyte was a NaCF3SO3 solution. The assembled button battery was subjected to an electrochemical performance test. The test results are shown in Table 1.
[0078] Table 1 First coulombic efficiency and specific capacity of sodium ion batteries made of corncob-based hard carbon materials
[0079]
[0080] As shown in Table 1, the sodium ion battery made of corncob-based hard carbon material prepared in Example 1 has a high conductivity at 300 mAg -1 The first coulombic efficiency is 97.54% at a current density of 300 mAg. -1 After 300 cycles at a current density of 20 mAg -1After 100 cycles at a current density of , it still has a good specific capacity, indicating that the sodium ion battery made of corncob-based hard carbon material prepared by the preparation method of the present invention not only has a high first coulombic efficiency, but also maintains a good specific capacity after multiple cycles.
[0081] The electrochemical performance test results of the sodium ion batteries made of corncob-based hard carbon materials prepared in Examples 2 and 3 are similar to those in Example 1.
[0082] Comparative Example 1 is a corncob-based hard carbon material without adding glucose. The sodium ion battery made from the material has a low initial coulombic efficiency, and its specific capacity after multiple cycles is not as good as that of Example 1.
[0083] Comparative Example 2 and Comparative Example 3 are respectively the cases where the temperature of the heat treatment insulation in step 4) is too low and too high, and the sodium ion battery made of the corncob-based hard carbon material obtained has a low initial coulombic efficiency and a low specific capacity after multiple cycles. The reason is that if the insulation temperature is too low or too high, it will affect the porosity and interlayer spacing of the corncob-based hard carbon material, which is not conducive to the storage and transmission of sodium ions, thereby reducing the initial coulombic efficiency of the sodium ion battery and the specific capacity after multiple cycles.
[0084] Comparative Example 4 is a case where the cooling rate in the process of decreasing from 1500°C to 600°C is not controlled in step 4), and the first coulombic efficiency of the sodium ion battery made of the corncob-based hard carbon material obtained is low. The reason is that rapid cooling after the 1500°C insulation treatment will cause the microstructure of the corncob-based hard carbon material to be destroyed, thereby reducing the first coulombic efficiency.
[0085] Figure 1 The sodium ion battery made of corncob-based hard carbon material prepared in Example 1 has a current of 20-1500 mAg -1 The charge and discharge rate performance diagram under current density. Figure 1 It can be seen that the corncob-based hard carbon material prepared in Example 1 has a high conductivity at 20, 30, 60, 120, 240, 300, 600, 900, and 1500 mAg -1 The reversible capacities obtained at the current densities were 305.3, 260.9, 251.6, 237.3, 213.9, 203.3, 165.4, 119.8, and 69.6 mAh g -1 Then when the current density returns to 20mAg -1 The reversible capacity can still return to 270mAhg -1 This indicates that the sodium ion battery made of the corncob-based hard carbon material prepared in the present invention has good rate performance.
[0086] Figure 2The sodium ion battery made of corncob-based hard carbon material prepared in Example 1 was 300 mAg -1 The charge and discharge cycle performance diagram under current density. Figure 2 It can be seen that the sodium ion battery made of corncob-based hard carbon material prepared in Example 1 has a high conductivity at 300 mAg -1 The specific capacity after 300 cycles at a current density of 237.4 mAh g -1 The first coulombic efficiency is 97.54%, which indicates that the sodium ion battery made of the corncob-based hard carbon material prepared in the present invention has a high first coulombic efficiency and a high specific capacity after multiple cycles.
[0087] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. A method for preparing a corncob-based hard carbon material, characterized in that: The following steps are involved: S1. corn cobs and monosaccharides are mixed to obtain a mixture; S2. carbonizing the mixture to obtain a carbonized material; S3. The carbonized material is heat treated and cooled to obtain the corncob-based hard carbon material; The heat treatment process in step S3 is: firstly heating the carbonized material to 1400-1500°C to keep the temperature, and then cooling it to 500-800°C at a rate of 1-3°C / min.
2. The preparation method according to claim 1, characterized in that: In step S1, the mass ratio of the corn cob to the monosaccharide is 1:(0.5-2).
3. The preparation method according to claim 1, characterized in that: In step S2, the carbonization temperature is 500-600°C.
4. The preparation method according to claim 1, characterized in that: In step S2, the carbonization time is 2 to 3 hours.
5. The preparation method according to claim 1, characterized in that: In step S2, the carbonization further includes pickling treatment.
6. The preparation method according to claim 1, characterized in that: In step S3, the heat treatment process is: firstly, the carbonized material is heated from room temperature to 1400-1500°C at a rate of 1-3°C / min for 2-3h, and then cooled to 500-800°C at a rate of 1-2°C / min.
7. A corncob-based hard carbon material, characterized in that: It is prepared by the preparation method according to any one of claims 1 to 6.
8. Use of the corncob-based hard carbon material according to claim 7 in preparing a negative electrode for a sodium ion battery.
9. A sodium ion battery negative electrode, characterized in that: The sodium ion battery negative electrode comprises the corncob-based hard carbon material according to claim 7.
10. A sodium ion battery, characterized in that: The sodium ion battery comprises the sodium ion battery negative electrode according to claim 9.
Citation Information
Patent Citations
Hard carbon composite material, as well as preparation method and application thereof
CN113422052A
Preparation method of waste biomass hard carbon negative electrode material for sodium ion battery
CN115417397A
Biomass hard carbon negative electrode material and preparation method and application thereof
CN117208886A
Lignin-based hard carbon negative electrode material with high rate capability as well as preparation and application of lignin-based hard carbon negative electrode material
CN117985681A
Hard carbon negative electrode material and preparation method and application thereof
CN118598112A
Cited By
Synthesis method of corncob-based hard carbon
CN122276706A